2000
DOI: 10.2190/apwf-n1xu-y7a0-tcbw
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol in Patients with Obsessive Compulsive Disorder during Treatment with Behavior Therapy and SSRI or Placebo

Abstract: Our data support the assumption that not only panic disorder but also other anxiety disorders, e.g., obsessive compulsive disorders, may be associated with serum cholesterol elevations. Effective treatment (behavior therapy and/or treatment with a selective serotonin reuptake inhibitor [SSRI]) seems to decrease cholesterol levels, especially in patients with pathological cholesterol elevations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
(57 reference statements)
2
12
0
1
Order By: Relevance
“…Several studies investigated the effect of FLV on plasma lipoprotein levels and reported that FLV may reduce serum cholesterol levels (51,52). In contrast, there have been few studies focused on the effect of plasma lipoprotein levels on FLV pharmacological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the effect of FLV on plasma lipoprotein levels and reported that FLV may reduce serum cholesterol levels (51,52). In contrast, there have been few studies focused on the effect of plasma lipoprotein levels on FLV pharmacological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmada anksiyete şiddeti ile serum lipid değerlerinin ilişkisini incelediğimizde, sadece LDL-kolesterol düzeyi ile anlamlı ilişki saptandı (p:0,031). Bizim çalışmamıza benzer şekilde anksiyete skoru ile serum lipid değerleri arasında anlamlı ilişki gösterilmiştir (46,47). Geniş çaplı bir araştırmada ise LDL-kolesterol düşüklüğü ile anksiyetenin şiddeti arasında anlamlı ilişki saptanmıştır (48).…”
Section: Gereç Ve Yöntemunclassified
“…Treatment with the SSRIs did not appear to result in increased cholesterol levels in one study (Bilici et al, 2001). In fact, the SSRIs appear to possess antihyperlipidemic effects (Bailey and LeMelledo, 2003;Peter et al, 2000;Sonawalla et al, 2001b). Treatment of depression with SSRIs was reported to decrease the activity of a number of antioxidative enzymes (glutathione reductase, glutathione peroxidase, malondialdehyde, superoxide dismutase) in one study (Bilici et al, 2001).…”
Section: Side-effect Profilementioning
confidence: 99%